Pengaruh kepemilikan institusional, kualitas audit, dan masa penugasan audit terhadap biaya pinjaman bank pada perusahaan industri penghasil bahan baku yang terdaftar di bei periode 2010-2012 - Janne Walandouw; Taufeni Taufik; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study is applied Empirical Study for all industrial companies that produce raw materials listed in Indonesia Stock Exchange 2010-2012. The purpose of this study is to determine influence of Institutional ownership, Audit Quality, and Tenure on the Cost of Bank Loan.The data was employed in this study is secondary data from industrial companies that produce raw materials listed in Indonesia Stock Exchange during 2010-2012. Purposive sampling method is taken and generates 30 companies as sample. Statistical analysis which used in this study is multiple regression method by SPSS version 17.00.The results show that Institutional Ownership, Audit Quality, and Tenure have significant influence of Cost of Bank Loan. Institutional Ownership shows 0.002 < 0.05 in significant result because Pvalue smaller than alpha score (0.05), Audit Quality shows 0.004 < 0.05 in significant result because Pvalue smaller than alpha score (0.05), and Tenure shows 0.018 < 0.05 in significant result because Pvalue smaller than alpha score (0.05). Based on the test result of the coefficient determination, the value of the Adjust R Square is 46.8% while the remaining 53.2% is influenced by other variables that are not included in this study such as audit committee, flexibility, corporate governance, organizational skill, etc.Keywords: Institutional Ownership, Audit Quality, Tenure, and Cost of Bank Loan